The Small World of Sammy Lee Based on a TV-Play by Ken Hughes - Hughes, Ken; Suschitzky, Wolfgang; Newley, Anthony; Stephens, Robert; Brambell, Wilfrid (The London Collection, 2009)
A 1963 British crime film directed by Ken Hughes and starring Anthony Newley, Julia Foster and Robert Stephens. "Small World of Sammy Lee" is just around any corner in Soho. Peopled by the pimps, the punters, the brasses and the bookies, and with boils on its face like the sleazy Peepshow club where Sammy (Anthony Newley) comperes the strip-tease. Sammy Lee is worried. When you owe £300 to a bookie like Conner you're entitled to be worried. Particularly when his muscle men (Kenneth J. Warren and Clive Colin Bowler) are coming in a few hours' time to collect the cash. Refused help from brother Lou (Warren Mitchell) by Lou's wife (Miriam Karlin) who won't pour the profits of their delicatessen into bookies’ pockets, Sammy is desperately setting up shady deals to raise the money. [www.amazon.co.uk]